Actual Problems of Organization of Dual Education in Professional Educational Institutions - Khasanova Holida Fattayevna (Journal of Innovation in Education and Social Research, 2024)
This article is devoted to considering the possibility of using the experience of dual education in the system of professional training of college and university students. The article discusses the specifics and benefits of dual learning. The tasks that need to be solved in the implementation of vocational education programs with elements of dual training to improve the efficiency of the quality of training qualified personnel from an institution of secondary vocational education and the subsequent successful employment of graduates.